CXCL10 and CCL2 mRNA expression in monocytes is inversely correlated with the HLA-DR lower fraction of monocytes in patients with renal cell carcinoma - MOTOSHIMA, TAKANOBU (Oncol Lett, 2016)
Circulating cluster of differentiation (CD)14+ human leukocyte antigen (HLA)-DRlow/- monocytes, those with a lower HLA-DR expression or are negative for HLA-DR, are considered to be involved in systemic immunosuppression in patients with several malignant tumors. However, few studies have investigated in detail the gene expression profile of CD14+HLA-DRlow/- monocytes. In the present study, the mRNA expression levels of immune-associated molecules in CD14+ monocytes isolated from healthy donors and patients with renal cell carcinoma (RCC) were analyzed. Consistent with previous studies, the percentage of HLA-DRlow/- cells in CD14+ monocytes was significantly increased in patients with RCC compared with healthy donors. In 3 of the 4 patients who underwent surgical resection of the primary tumor, the percentage of CD14+HLA-DRlow/- cells was significantly decreased following surgery. The mRNA expression levels of cyclooxygenase 2, transforming growth factor β, interleukin 6R, chemokine (C-C motif) ligand 2 (CCL2), chemokine (C-X-C motif) ligand 10 (CXCL10), oncostatin M, and vascular endothelial growth factor-A in CD14+ monocytes were quantified using reverse transcription-quantitative polymerase chain reaction. The results of the present study revealed that increased expression levels of CCL2 and CXCL10 were inversely correlated with the percentage of CD14+HLA-DRlow/- monocytes. This suggested that monocytes in RCC patients were immunologically suppressed, and that immunosuppression in RCC patients may be due, in part, to the dysfunction of circulating monocytes.